Learning Transformation in the Human and Natural Resources Economics course through the GPT Chat: A Reviewâ€ - Paulus L Wairisal (Jurnal Penelitian Pendidikan IPA, 2023)
In the world of education, we are led to carry out learning that is easy to understand and carried out by many developments in the field of technology. Where the purpose of the research is to explain Learning Transformation in the Human and Natural Resources Economics course through the GPT Chat. In the Human and Natural Resources Economics course, the use of GPT Chat can provide convenience for students in carrying out the learning transformation process. A review is conducted on the state-of-the-art methods using the preferred reporting items for reviews and meta-analyses (PRISMA) guidelines. In the world of education, we are led to carry out learning that is easy to understand and carried out by many developments in the field of technology. One of the learning transformations is to use AI as a technology that can help humans achieve greater progress and open up new opportunities for innovation and success in various fields. Especially in human resource and natural resource economics courses, digital-based learning transformation using GPT chat can simplify and access the information needed in the learning process.